Vitamin D3 Level and Its Receptor of Patients with Psoriasis: A Case Control Study - Abdulsamie Hassan Altaee (Journal of Global Pharma Technology, 2018)
Psoriasis is multi-factorial disease resulted in response to increase secretion of inflammatory cytokines or deficiency in certain vitamins such as vitamin D3. This study aims to evaluate the levels of vitamin D3 and its receptor (VDR) in psoriatic patients and healthy control, additionally to determine the ratio between vitamin/receptor and their relative risk in the pathogenesis of psoriasis. This study was design as a case-control study and includes 45 psoriatic subjects and 45 healthy controls. The results of currents study were found a significant decrease in vitamin D3, VDR levels and vitamin D3/ VDR ratio when compared with the healthy control group. The relative risk for VDR levels with psoriasis found to be positively significantly associated, whereas those for vitamin D3 levels with psoriasis were insignificant. In conclusion, the relative risk for VDR is more than that for calicitriol and this support the pathogenic role of VDR abnormality in psoriasis.Key words: Vitamin D, Vitamin D receptor, Psoriasis, Keratinocyte, Babylon.